Evaluation of Acute Alcohol Intoxication as the Primary Cause of Death: A Diagnostic Challenge for Forensic Pathologists1. Issue 5 (25th January 2017) - Li, Rong; Hu, Li; Hu, Lingli; Zhang, Xiang; Phipps, Rebecca; Fowler, David R.; Chen, Feng; Li, Ling
Abstract: Deaths caused by acute alcohol intoxication (AAI) remain a major public health issue. This study is retrospective and descriptive: an 8‐year case analysis of deaths due to AAI in Maryland. Study showed that of 150 AAI deaths, the death rate among Hispanics (10.41/100, 000 population) was significantly higher than all the non‐Hispanics combined (1.88/100, 000 population). The majority of individuals were young adults, overweight, and binge drinkers. The obese group showed significantly lower mean heart and peripheral blood alcohol concentration (BAC) (0.36%, 0.37%) than the normal weight group (0.45%, 0.42%). Based on the PBAC and urine AC ratio, 49.6% deaths likely occurred close to peak phase, followed by postabsorptive phase (31.6%) and absorptive phase (18.8%). Our results indicate that forensic pathologists should evaluate postmortem BAC in the light of individual's age, drinking history, body weight, possible phase of alcohol intoxication, and other autopsy findings when certifying AAI as primary cause of death.